The Role Of Supervision And Work Discipline On Employee Performance - Sudarajat, Yayat (SEIKO : Journal of Management & Business, 2023)
The purpose of this study is to assess the impact of supervision and work discipline on employee performance at the Achilles Tyre Warehouse of PT Matsuoka Industries Indonesia. The study is quantitative in nature. The research population included 45 PT Matsuoka Industries Indonesia employees. The sample size was 45 persons, with an 88% confidence level. In this study, a questionnaire was employed to collect data. SPSS V26 is used to test sample data. Validity tests, reliability tests, normalcy tests, F tests, and T tests were utilised in the investigation. The findings of this study indicate that H2 is acknowledged, implying that there is a positive and significant relationship between supervision and work discipline on employee performance at the same time. Keywoard: Supervision, Work Discipline, Employee Performance